Electro-optical properties of polymeric "guest-host" system doped with 8-hydroxyquinoline azo dyes and its cobalt complexes - Davidenko, N.A.; Davidenko, I.I.; Savchenko, I.A.; Sinyugina, A.T.; Studzinsky, S.L.; Popenaka, A.N.; Tonkopieva, L.S.; Kolendo, A.Yu.; Ankin, A.N. (Functional Materials, 2009)
Polymeric composites based on the butyl methacrylate: nonyl methacrylate (3:1) copolymer doped with 8-hydroxyquinoline azo dyes with donor and acceptor substituents and the cobalt complexes thereof have been obtained. The influence of an external electric field on the polymeric film transmission of linearly polarized light in the long-wave part of the azo dye absorption range (corresponding to ππ* azo fragment absorption range) and their metal complexes have been revealed. The influence of the electric field on the transmission is connected with the forces acting on dipole moments of azobenzene groups and metal ions. Одержано полімерні композити на основі співполімеру бутилметакрилат:нонілметакрилат (3:1) з домішками азобарвників на основі 8-оксихіноліну з донорним і акцепторним замісниками та їх комплексів з кобальтом. Виявлено вплив зовнішнього електричного поля на пропускання полімерними плівками лінійно поляризованого світла на довгохвильовій межі поглинання азобарвників (яка відповідає ππ* смузі поглинання азофрагментів) та їх металокомплексів. Вплив електричного поля на пропускання світла пояснюється виникненням сил, які діють на дипольні моменти азобензольних груп і на іони металу. Получены полимерные композиты на основе сополимера бутилметакрилат:нонилметакрилат (3:1) с добавками азокрасителей на основе 8-оксихинолина с донорным и акцепторным заместителями и их комплексов с кобальтом. Обнаружено влияние внешнего электрического поля на пропускание полимерными пленками линейно поляризованного света на длинноволновом краю поглощения азокрасителей (соответствующем ππ* полосе поглощения азофрагментов) и их металлокомплексов. Влияние электрического поля на пропускание света объясняется возникновением сил, действующих на дипольные моменты азобензольных групп и на ионы металла.